Faktor yang berhubungan dengan Penggunaan Jamban di Desa Sungai Terap Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - T Samsul Hilal; Ahmad Husaini; Andi Ahmadiyah Nurussabil (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
The use of latrines in the village is still unhealthy because of the habits of the people who use pit latrines in the river and the people in the terap river themselves use dug wells as a source of clean water where there is still insufficient clean water, the impact of not using latrines is causing environmental-based diseases, causing odor , and cause pollution. Access to latrines in Indonesia 79.42% Jambi Province 84.26% Muaro Jambi Regency 89.35 and Sungai Terap Village 77.93%. This research used quantitative methods with cross sectional approach. The population in this study were all family heads of the Sungai Terap Village community as many as 550 families. The sample in this study were 90 respondents. The sampling technique was simple random sampling. This research was conducted in July 2020. Data were obtained by means of interviews using questionnaires, observations and checklist sheets. Data were analyzed univariate and bivariate using the chi-square test. The results of this study indicate that there is a relationship between clean water facilities (p-value = 0,000), community leaders (p-value = 0,000), and knowledge (p-value = 0.002). Meanwhile, there is no relationship between education (p-value = 0.957) and the role of health workers (p-value = 0.189) and the use of latrines. It is hoped that health workers can trigger STBM to the community about the importance of using latrines and the impact if people do not use latrines so that people's knowledge about latrines can increase, so that it can change people's behavior